Polyamine Uptake, Kinetics, and Competition among Polyamines and between Polyamines and Inorganic Cations - Pistocchi, Rossella (1986)
Polyamine uptake, the kinetics of this uptake, and the competition among polyamines and between polyamines and inorganic cations were studied in petals of Saintpaulia ionantha Wendl. Uptake experiments using (14)C-labeled polyamines were carried out on single petals, at room temperaure (20°C) and in the light. The results show that putrescine, spermidine, and spermine uptake was dependent on the external pH and occurred up to high external polyamine concentrations with K(m) values of 8.6, 1.2, and 2.1 millimolar, respectively, with spermidine being the most absorbed at low concentration (17 micromolar). Putrescine and spermidine did not seem to compete for the same site of absorption. Furthermore, putrescine and spermidine uptake was not inhibited by Ca(2+), Mg(2+), and K(+) at the same concentrations (17 micromolar), whereas 1.7 millimolar Ca(2+) inhibited and K(+) enhanced spermidine uptake. The intracellular localization of the absorbed putrescine was determined using two different methods. Very little label was found in the apoplast, while most of it was localized in the 98,500g supernatant. According to our data the vacuole, which represents a substantial part of Saintpaulia parenchyma cells, could be a site of putrescine accumulation. 2,4-Dinitrophenol and diethylstilbestrol did not inhibit uptake; however, at 0°C there was a 35% inhibition of spermidine uptake, compared with the controls kept at 20°C as well as a 68% inhibition with 20 millimolar NaSCN.